Multicolor Two‐Photon Nanosystem for Multiplexed Intracellular Imaging and Targeted Cancer Therapy. Issue 22 (17th May 2021) - Wu, Yong‐Xiang; Zhang, Dailiang; Hu, Xiaoxiao; Peng, Ruizi; Li, Junbin; Zhang, Xiaobing; Tan, Weihong
Abstract: The novel theranostic nanosystems based on two‐photon fluorescence can achieve higher spatial resolution of deep tissue imaging for simultaneous diagnosis and therapy of a variety of cancers. Herein, we have designed and prepared FRET‐based two‐photon mesoporous silica nanoparticles (MTP–MSNs) for single‐excitation multiplexed intracellular imaging and targeted cancer therapy for the first time. This nanosystem includes two constituents, containing (1) multicolor two‐photon mesoporous silica nanoparticles and (2) cancer cell‐targeting aptamers that act as gatekeepers for MTP–MSNs. After incubation with cancer cells, the Dox‐loaded and aptamer‐capped MTP–MSNs could be internalized into the cells, opening the pores and releasing the drug. Furthermore, using two‐photon multicolor fluorescence, MTP–MSNs could serve as good contrast agents for multicolor two‐photon intracellular imaging with increased imaging depth and improved spatial localization of tissue. In sum, these multicolor MTP–MSNs provide a promising system for traceable targeted cancer therapy with further applications in multiplex intracellular imaging and the screening of drug. Abstract : Herein, we have designed and prepared FRET‐based two‐photon mesoporous silica nanoparticles (MTP–MSNs) for multiplexed intracellular imaging and targeted cancer therapy for the first time. After incubation with cancer cells, MTP–MSNs could release drugs and performed multicolor two‐photon cellular imaging. These MTP–MSNs provide a promising system for traceable targeted cancer therapy with further applications in multiplex intracellular imaging.